Field evaluation of the combination of lincomycin and spectinomycin for the treatment of foot rot in sheep - ΣΠΑΗΣ Α. Γ.; ΑΡΓΥΡΟΥΔΗΣ Σ. (Journal of the Hellenic Veterinary Medical Society, 2019)
The combination of the antibiotics lincomycin and spectinomycin in 3 flocks of sheep, affected from Foot-Rot was tested. A serie of 3 intramuscular injections, once daily, of 5 mg /kg b.w. of lincomycin and 10 mg/kg b.w. spectinomycin, was used. From the results of this study it is concluded that the combination of the above two antibiotics is very effective in the treatment of Foot-Rot. The effectiveness with complete recovery of the sick animals, irrespective of the course of the disease, is estimated to amount up to 95%. Relapses after some time may occur. Also in one flock slight digestive side effects, after the 1st injection, have been observed.